Amantadine toxic effect and acute psychosis – a case report - Gruca, Dariusz; Antoniak, Krzysztof; Wais, Marcin; Zając, Marlena (Journal of Education, Health and Sport, 2023)
Introduction and purpose: The pandemic of COVID-19 has induced patients to use different ways to struggle with SARS-CoV-2 infection. Amantadine has become more popular as a supportive drug in the treatment of COVID-19 symptoms. This report presents a case of a young, previously healthy woman hospitalized in the Toxicology and Cardiology Department because of acute psychosis induced by amantadine intoxication. Brief description of the state of knowledge: Several medications, including psychostimulants, antibiotics, antivirals, and antiparkinsonians can cause acute psychosis. Amantadine has primarily dopaminergic with some anticholinergic properties and is used predominantly as an adjuvant agent in the management of Parkinson’s disease treatment. Psychomotor agitation, insomnia, excessive verbosity, delusions, and behavioral disturbances are typical toxic effects of amantadine primarily affecting the central nervous system presented by the patient described in this case report. Conclusions: Our case illustrates the adverse effects of amantadine on the central nervous system when given at the recommended dose to young, healthy women. Despite being rare, this induced psychosis may become more common, especially while becoming more popular as a supportive drug in COVID-19 treatment. While prescribing amantadine clinicians should be aware of the rapid onset of its psychotic complications.